Pengaruh Variasi Temperatur Reaktor terhadap Hasil Produk Pirolisis Eceng Gondok Secara Ex-Situ dengan Katalis Bentonit dan Penambahan Uap Air - Hamidi, Nurkholis; Firmansyah, Anggi; Kusumaningsih, Haslinda (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
The water hyacinth has high growth rates that can lead to various environmental problems and the production of large amounts of waste biomass. However, it can be a source of lignocellulosic biomass for the production of bio-oil. This study aims to determine the effect of temperature variation on the pyrolysis process of water hyacinth ex-situ with bentonite catalyst and the addition of water vapor. Temperature variations used are 450°C, 550°C, and 650°C. The pyrolysis process uses 300 grams of water hyacinth and is carried out for 1 hour. The results showed that increasing pyrolysis temperature reduced the char and bio-oil products, but increased the product of gas. Pyrolysis at 450°C produces a lot of bio-oil, while at the temperature of 650°C tends to produce gas products. Also, increasing the pyrolisis temperature results in a higher density of bio-oil. Gas chromatograph testing was carried out to determine the content of organic compounds found in bio-oil. Hydrocarbons are obtained which increase with increasing temperature. The highest percentage of the content of organic compounds is in oxygen compounds. Components of alcohol, phenols, ketones, aldehydes are functional compounds found in the content of bio-oil. Acid compounds are also contained in bio-oil from the results of pyrolysis of water hyacinth.